Association of litter size with sex hormones and body measurements of Iraqi awassi ewes - Al-Thuwaini, Tahreer M.; Al-Shuhaib, Mohammed Baqur S.; Imran, Faris Sahib (Journal of Kerbala for Agricultural Sciences, 2020)
Litter size is the most important reproductive trait in sheep production, which is influenced by the ovulation rate, a few hormones, and the fecundity genes. Ewe reproductive performance is known to be affected by body measurements. Therefore, this study aims to investigate the possibility of an association between the litter size with sex hormones and body measurements in Iraqi Awassi ewes. A total of 224 sexually mature ewes, non-pregnant, non-lactation and healthy (124 ewes with single birth and 100 ewes with twin birth), aged between 2.5 to 5 years were included in this study. Blood samples were collected from the sheep, and then the serum was separated from blood to determine the concentrations of the estradiol and progesterone. Live body weight and body measurements were determined for each animal. The result of the present study refers that the live body weight of Awassi ewes was significantly (P<0.05) influenced in the litter size. The association analysis of litter size with body measurements indicated that the neck length, height at hip and chest girth were different for the type of birth of Awassi ewes. The highest positive correlation (P < 0.01) was recorded among litter size with live body weight (r=0.698, P=0.001), with height at shoulder (r=0.242, P=0.031) and height at hip (r=0.309, P=0.005).In conclusion, the litter size of Awassi ewes is influenced by the other phenotypic traits. The ewes with heavier live body weight and higher body measurements are more favorable to having more lambs than ewes with a single birth.